Регенерация цибридных растений Lycopersicon peruvianum × (Solanum rickii) с трансформированными хлоропластами - Матвеева, Н.А.; Момот, В.П.; Шаховский, А.М.; Кучук, Н.В. (Цитология и генетика, 2005)
В результате эксперимента по γ-слиянию мезофильных протопластов хлорофиллдефектного мутанта Lycopersicon peruvianum и транспластомного растения Solanum rickii на селективной среде, содержавшей антибиотики спектиномицин и стрептомицин, были получены гибридные растения, имеющие трансформированные хлоропласты S. rickii и ядерный геном L. peruvianum, что подтверждено результатами ПЦР-анализов. The hybrid plants with transformed plastids were regenerated after PEG fusion of chlorophyll-deficient Lycopersicon peruvianum leaf mesophyll protoplasts and leaf mesophyll protoplasts of Solanum rickii, which were previously genetically transformed and as the result were resistant to streptomycine and spectinоmycine. The hybrid callus selection was based on the inability of the Lycopersicon peruvianum minicalli to have the green coloration and on the inability of gamma-preirradiated Solanum rickii protoplasts to divide. The hybrids were identified on the base of PCR analyses of nuclear and plastid DNA.